(untitled) (Research, Society and Development, 2021)
Objective: to analyze the performance of Nursing in the context of Palliative Care. Methodology: this is an observational, cross-sectional study with a qualitative approach, carried out in the context of secondary health care, in an Emergency Care Unit in a city in the Midwest of São Paulo. Data collection took place in the first semester of 2020, through an interview with an instrument prepared by the authors, composed of questions for the characterization of the participants and about the perception regarding assistance in palliative care. The collected data were analyzed using content analysis, categorical thematic modality. Results: 12 mid-level nursing professionals participated, with an average age of 33 years, mostly female (91.7%). Three categories were chosen: 1. Training in palliative care; 2 - Knowledge about palliative care; 3 - Performance in palliative care. Final considrations: the present study made it possible to understand the difficulty that nursing professionals encounter when faced with the theme of palliative care. Some professionals showed a lack of knowledge, both theoretical and practical, about the assistance needed for this type of care. In addition to the lack of knowledge on the part of some; others showed a strong sensitivity in relation to the theme. Despite knowing that death is present in the daily lives of these nursing professionals, many do not consider themselves prepared for this moment.